Multi-element micro-alloyed high-forming corrosion-resistant and heat-resistant magnesium alloy and preparation method thereof
Patent Information
- Application Number
- CN202611361042.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]本发明的目的在于针对现有低合金Mg-Zn系镁合金板材基面织构较强、力学性能各向异性明显、室温冲压成形性能不足,以及强度、耐腐蚀性能和高温组织稳定性难以兼顾等问题,提供一种多元微合金化高成形耐蚀耐热镁合金及其制备方法
[0020](1)本发明采用Zn、Sm、Mn、Y和Ca多元素协同微合金化设计,能够在镁基体中形成弥散分布的纳米析出相和块状(Mg,Zn)3Sm微米相。弥散纳米析出相能够阻碍位错运动并产生析出强化作用,第二相及细化晶粒能够共同提高合金板材的强度,实现细晶强化和析出强化的协同作用。本发明添加的Mn元素可与熔体中铁杂质结合形成高熔点金属间化合物沉降分离,Y元素可与熔体内部氧、铁杂质发生反应,生成高熔点的稀土氧化物及稀土-铁金属间化合物,部分化合物上浮成渣或沉降于坩埚底部,从而实现熔体杂质净化。
Smart Images

Figure CN122979724A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal material processing technology, specifically to a multi-element microalloyed high formability, corrosion resistance, and heat resistance magnesium alloy and its preparation method. Background Technology
[0002] Magnesium alloys possess advantages such as low density, high specific strength and stiffness, good electromagnetic shielding performance, and ease of recycling, making them promising for lightweight applications in areas like structural components for new energy vehicles, housings for electronic products, and heat dissipation components. However, magnesium has a close-packed hexagonal crystal structure, resulting in a limited number of independently activating slip systems at room temperature and limited plastic deformation capacity. During the rolling process, magnesium alloy sheets tend to develop strong basal textures, leading to increased differences in mechanical properties between the rolling direction and the transverse direction. This results in defects such as earing, localized thinning, and cracking during subsequent stamping, limiting the large-scale application of magnesium alloy thin-plate components.
[0003] Mg-Zn alloys are characterized by low alloying degree, relatively low raw material cost, and significant precipitation strengthening potential, making them an important system for developing low-cost wrought magnesium alloys. However, conventional low-alloy Mg-Zn plates typically exhibit strong basal texture and significant anisotropy in mechanical properties after rolling, and their room-temperature formability still needs improvement. Furthermore, the number of effective strengthening phases that can be formed under low-alloying conditions is limited, and the size, morphology, and distribution of precipitates are difficult to control effectively, thus hindering the synergistic improvement of strength, plasticity, and formability.
[0004] Furthermore, magnesium alloys exhibit high chemical reactivity and are prone to corrosion in corrosive media containing chloride ions. Coarse, continuous, or unevenly distributed second phases in the alloy can also form microcouples with the magnesium matrix, accelerating localized corrosion. During long-term service at high temperatures, magnesium alloy sheets may experience grain growth, coarsening or dissolution of precipitates, and softening of the microstructure, leading to a decrease in their mechanical properties and dimensional stability. Therefore, while improving the formability of the sheet, rationally controlling the type, size, and distribution of the second phase is of great significance for enhancing the corrosion resistance and high-temperature microstructural stability of magnesium alloys.
[0005] Existing technologies typically weaken the basal texture and improve the strength and thermal stability of alloys by adding higher amounts of rare earth elements or multiple high-cost alloying elements. However, these alloys generally suffer from high alloying degrees, high raw material costs, and complex smelting control, which are not conducive to the mass production of thin sheet products. Although some low-alloy magnesium alloys have improved mechanical properties through rolling and heat treatment, their process parameter control range is narrow. When the rolling temperature, pass reduction, or annealing regime is unreasonable, it is easy to cause abnormal grain growth, second-phase agglomeration, or coarsening of precipitates, making it difficult to simultaneously achieve the formability, corrosion resistance, and heat resistance of the sheet material.
[0006] Therefore, it is still necessary to develop a magnesium alloy with a low degree of alloying, a small amount of rare earth elements, and a simple and controllable preparation process. Through the synergistic design of multi-element microalloying and rolling heat treatment processes, the grain structure, texture, and second phase distribution can be controlled to obtain magnesium alloy sheets with good stamping performance, corrosion resistance, and high-temperature structural stability. Summary of the Invention
[0007] The purpose of this invention is to address the problems of existing low-alloy Mg-Zn magnesium alloy sheets, such as strong basal texture, significant anisotropy in mechanical properties, insufficient room temperature stamping formability, and difficulty in simultaneously achieving strength, corrosion resistance, and high-temperature microstructure stability. This invention provides a multi-element microalloyed high-formability, corrosion-resistant, and heat-resistant magnesium alloy and its preparation method. Through the synergistic alloying design of Zn, Sm, Mn, Y, and Ca elements, combined with homogenization, rolling, and annealing processes, the microstructure, texture, and second-phase distribution of the alloy are synergistically controlled, thereby obtaining magnesium alloy sheets with good formability, corrosion resistance, and high-temperature microstructure stability.
[0008] To achieve the above objectives, the present invention adopts the following technical solution.
[0009] A multi-element microalloyed high-formability, corrosion-resistant, and heat-resistant magnesium alloy, by mass percentage, is composed of the following components: Zn 1.5%, Sm 1.0%, Mn 0.2%, Y 0.4%, Ca 0.1%, with unavoidable impurities totaling no more than 0.05%, and the balance being Mg; the total mass fraction of alloying elements in the magnesium alloy is 3.2%.
[0010] A method for preparing a multi-element micro-alloyed high-formability, corrosion-resistant, and heat-resistant magnesium alloy includes the following steps:
[0011] S1, Casting: Prepare pure Mg, pure Zn, Mg-Sm master alloy, Mg-Mn master alloy, Mg-Y master alloy, and Mg-Ca master alloy according to the composition ratio of the magnesium alloy; melt pure Mg under a mixed protective atmosphere composed of CO2 and SF6 to obtain magnesium liquid; add the remaining raw materials except pure Mg to the magnesium liquid in batches after preheating at 100-200 °C for 30-100 min; after the addition is completed, heat the magnesium liquid to 700-720 °C and hold for 5-10 min, then purge with argon gas for refining, remove slag and let stand, then pour the magnesium liquid into a mold preheated to 220-240 °C, and obtain magnesium alloy ingots after cooling; wherein, the volume fraction of CO2 in the mixed protective atmosphere is 80%-90% and the volume fraction of SF6 is 10%-20%;
[0012] S2, Homogenization treatment: The magnesium alloy ingot obtained in S1 is subjected to homogenization treatment, and then water quenched to room temperature to obtain a homogenized magnesium alloy ingot.
[0013] S3, Rolling and Annealing: The homogenized magnesium alloy ingot obtained in S2 is rolled and then annealed to obtain the multi-element micro-alloyed high formability, corrosion resistance and heat resistance magnesium alloy sheet.
[0014] Preferably, in step S1, the added Mn element combines with iron impurities in the melt to form high-melting-point intermetallic compounds that settle and separate, while the Y element reacts with oxygen and iron impurities in the melt to generate high-melting-point rare earth oxides and rare earth-iron intermetallic compounds, some of which float to the surface as slag or settle, thereby purifying the impurities in the melt.
[0015] Preferably, in step S2, the homogenization treatment temperature is 500 ℃, the holding time is 8 h, and the homogenization treatment is completed by water quenching to room temperature.
[0016] Preferably, in step S3, the rolling process adopts a unidirectional rolling process. The initial thickness of the plate before rolling is 5 mm, and the target thickness of the plate after rolling is 1.5 mm. Before each rolling pass, the plate is kept at 320 ℃ for 10 min. Except for the last pass, the single-pass reduction rate is 15%, and the reduction rate of the last pass is adjusted according to the target thickness.
[0017] Preferably, in step S3, the annealing temperature is 420 °C, the holding time is 30 min, and water cooling is performed after the annealing process.
[0018] Preferably, the obtained magnesium alloy sheet has an Eriksen cupping value of 7.6 mm; after being immersed in a 3.5% NaCl aqueous solution for 7 days, the average corrosion rate of the magnesium alloy sheet, measured by the hydrogen evolution method, is 1.16 mm / year; and after being exposed at 200℃ for 1000 hours, there is no significant decrease in strength and plasticity.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) This invention employs a multi-element synergistic microalloying design with Zn, Sm, Mn, Y, and Ca, which can form dispersed nano-precipitates and bulk (Mg,Zn)3Sm micron phases in a magnesium matrix. The dispersed nano-precipitates can hinder dislocation movement and produce precipitation strengthening. The second phase and refined grains can jointly improve the strength of the alloy sheet, achieving a synergistic effect of grain refinement strengthening and precipitation strengthening. The Mn element added in this invention can combine with iron impurities in the melt to form high-melting-point intermetallic compounds that settle and separate. The Y element can react with oxygen and iron impurities inside the melt to generate high-melting-point rare earth oxides and rare earth-iron intermetallic compounds. Some of these compounds float to the surface as slag or settle at the bottom of the crucible, thereby achieving the purification of impurities in the melt.
[0021] (2) The dispersed second phase formed by the present invention can pin grain boundary migration and inhibit abnormal grain growth and microstructure coarsening during high-temperature heat exposure. The magnesium alloy plate prepared can still maintain a relatively stable microstructure and room temperature mechanical properties after heat exposure at 200 ℃ for 1000 h, and has good heat resistance and long-term microstructure stability.
[0022] (3) The total amount of rare earth elements added in this invention is relatively low, which can reduce raw material costs and alloying degree compared with rare earth magnesium alloys with high Sm or high Y content. The magnesium alloy does not contain Al, thus avoiding the formation of Al-related β-Mg. 17 Al 12 The phase and its potential adverse effects on plastic processing and corrosion resistance.
[0023] (4) The present invention employs a homogenization treatment of 500 ℃ for 8 h, which can promote the dissolution of the coarse second phase in the as-cast state, reduce element segregation and improve the uniformity of the alloy structure, and at the same time provide solute conditions for precipitation behavior in subsequent rolling and heat treatment processes.
[0024] (5) The present invention adopts a 320 ℃ unidirectional rolling process, which promotes dynamic recrystallization and grain refinement by accumulating deformation energy through inter-pass heat preservation and multi-pass deformation; the 420 ℃ short-time annealing after rolling can reduce residual stress, regulate recrystallization structure and basal texture, reduce the difference in mechanical properties between the rolling direction and the transverse direction, thereby improving the room temperature stamping performance of the plate.
[0025] (6) The smelting, homogenization, rolling and annealing processes of the present invention are reasonably connected, the tendency of edge cracking of the sheet is low during the preparation process, and the finished product has uniform thickness, which is suitable for the stable preparation of magnesium alloy thin sheets. The obtained sheet has good stamping forming performance, corrosion resistance and heat resistance, and can be used for the preparation of structural parts for new energy vehicles, housings of electronic products, electronic heat dissipation components and other lightweight thin sheet components. Attached Figure Description
[0026] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments are briefly introduced below. Obviously, the following drawings only show some embodiments of the present invention. For those skilled in the art, other related drawings can be obtained based on these drawings without any creative effort.
[0027] Figure 1 The room temperature tensile stress-strain curve of the multi-element microalloyed high formability, corrosion resistance and heat resistance magnesium alloy sheet prepared in Example 1 of the present invention and the physical image of the sample after the Eriksen cupping test.
[0028] Figure 2The average corrosion rate of the multi-element microalloyed high formability corrosion-resistant and heat-resistant magnesium alloy sheet prepared in Example 2 of the present invention was measured by hydrogen evolution method and weight loss method after immersion in 3.5% NaCl aqueous solution for 7 days.
[0029] Figure 3 The room temperature engineering stress-engineering strain curve of the multi-element microalloyed high formability, corrosion resistance and heat resistance magnesium alloy sheet prepared in Example 3 of the present invention after heat exposure at 200 ℃ for 1000 h. Detailed Implementation
[0030] To make the objectives, technical solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be noted that the following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of this invention. Equivalent substitutions, simple modifications, or improvements made by those skilled in the art without departing from the concept of this invention should all fall within the scope of protection of this invention.
[0031] Unless otherwise stated, the content of each alloying element in the embodiments of the present invention is a mass percentage.
[0032] Example 1:
[0033] This embodiment prepares a Mg-1.5Zn-1Sm-0.2Mn-0.4Y-0.1Ca alloy. By mass percentage, the alloy consists of the following components: Zn 1.5%, Sm 1.0%, Mn 0.2%, Y 0.4%, Ca 0.1%, with unavoidable impurities totaling no more than 0.05%, and the balance being Mg.
[0034] The preparation method of the alloy includes the following steps:
[0035] S1: Melting and Casting: Prepare pure Mg, pure Zn, Mg-Sm master alloy, Mg-Mn master alloy, Mg-Y master alloy, and Mg-Ca master alloy according to the above alloy composition ratio. Melt under a mixed protective atmosphere composed of CO2 and SF6, wherein the volume fraction of CO2 is 80%–90% and the volume fraction of SF6 is 10%–20%.
[0036] Pure Mg is preheated at 300–400 °C for 30–90 min, then heated to 680–695 °C until completely melted to obtain molten magnesium. Pure Zn, Mg-Sm master alloy, Mg-Mn master alloy, Mg-Ca master alloy, and Mg-Y master alloy are preheated at 100–200 °C for 30–100 min, and then added in batches to the molten magnesium according to the alloy composition ratio. After the addition is complete, the alloy melt is heated to 700–720 °C and held at that temperature for 5–10 min, then refined by introducing argon gas. After refining, slag is removed and the mixture is allowed to stand. The alloy melt is then poured into a mold preheated to 220–240 °C, and after cooling, magnesium alloy ingots are obtained.
[0037] S2: Homogenization treatment: The magnesium alloy ingot obtained in step S1 is heated to 500 ℃ and held for 8 h, and then water-quenched to room temperature to obtain a homogenized magnesium alloy ingot.
[0038] S3: Rolling and Annealing: The homogenized magnesium alloy ingot obtained in step S2 is processed into a slab with an initial thickness of 5 mm, and then rolled to the target thickness of 1.5 mm using a unidirectional rolling process. Before each rolling pass, the slab is held at 320 ℃ for 10 min; except for the last pass, the reduction rate per pass is approximately 15%, and the reduction rate of the last pass is adjusted according to the target thickness.
[0039] After rolling, the plate is heated to 420 ℃ and held for 30 min, then water-cooled to room temperature to obtain annealed Mg-1.5Zn-1Sm-0.2Mn-0.4Y-0.1Ca alloy plate.
[0040] According to the test, the Eriksen cupping value of the annealed Mg-1.5Zn-1Sm-0.2Mn-0.4Y-0.1Ca alloy sheet prepared in this embodiment is 7.6 mm.
[0041] Example 2:
[0042] This embodiment prepares a Mg-1.5Zn-1Sm-0.2Mn-0.4Y-0.1Ca alloy. By mass percentage, the alloy consists of the following components: Zn 1.5%, Sm 1.0%, Mn 0.2%, Y 0.4%, Ca 0.1%, with unavoidable impurities totaling no more than 0.05%, and the balance being Mg.
[0043] The preparation method of the alloy includes the following steps:
[0044] S1: Melting and Casting: Prepare pure Mg, pure Zn, Mg-Sm master alloy, Mg-Mn master alloy, Mg-Y master alloy, and Mg-Ca master alloy according to the above alloy composition ratio. Melt under a mixed protective atmosphere composed of CO2 and SF6, wherein the volume fraction of CO2 is 80%–90% and the volume fraction of SF6 is 10%–20%.
[0045] Pure Mg is preheated at 300–400 °C for 30–90 min, then heated to 680–695 °C to completely melt it, yielding molten magnesium. Pure Zn, Mg-Sm master alloy, Mg-Mn master alloy, Mg-Y master alloy, and Mg-Ca master alloy are preheated at 100–200 °C for 30–100 min, and then added in batches to the molten magnesium according to the alloy composition ratio. After the addition is complete, the alloy melt is heated to 700–720 °C and held for 5–10 min, followed by refining with argon gas. After refining, slag is removed and the mixture is allowed to stand. The alloy melt is then poured into a mold preheated to 220–240 °C, and after cooling, a magnesium alloy ingot is obtained.
[0046] S2: Homogenization treatment: The magnesium alloy ingot obtained in step S1 is heated to 500 ℃ and held for 8 h, and then water-quenched to room temperature to obtain a homogenized magnesium alloy ingot.
[0047] S3: Rolling and Annealing: The homogenized magnesium alloy ingot obtained in step S2 is processed into a slab with an initial thickness of 5 mm, and then rolled to the target thickness of 1.5 mm using a unidirectional rolling process. Before each rolling pass, the slab is held at 320 ℃ for 10 min; except for the last pass, the reduction rate per pass is approximately 15%, and the reduction rate of the last pass is adjusted according to the target thickness.
[0048] After rolling, the plate is heated to 420 ℃ and held for 30 min, then water-cooled to room temperature to obtain annealed Mg-1.5Zn-1Sm-0.2Mn-0.4Y-0.1Ca alloy plate.
[0049] The annealed Mg-1.5Zn-1Sm-0.2Mn-0.4Y-0.1Ca alloy sheet prepared in this embodiment had an Eriksen cupping value of 7.6 mm. After immersion in a 3.5% NaCl aqueous solution for 7 days, the average corrosion rate measured by the hydrogen evolution method was 1.16 mm / year.
[0050] Example 3:
[0051] This embodiment prepares a Mg-1.5Zn-1Sm-0.2Mn-0.4Y-0.1Ca alloy. By mass percentage, the alloy consists of the following components: Zn 1.5%, Sm 1.0%, Mn 0.2%, Y 0.4%, Ca 0.1%, with unavoidable impurities totaling no more than 0.05%, and the balance being Mg.
[0052] The preparation method of the alloy includes the following steps:
[0053] S1: Melting and Casting: Prepare pure Mg, pure Zn, Mg-Sm master alloy, Mg-Mn master alloy, Mg-Y master alloy, and Mg-Ca master alloy according to the above alloy composition ratio. Melt under a mixed protective atmosphere composed of CO2 and SF6, wherein the volume fraction of CO2 is 80%–90% and the volume fraction of SF6 is 10%–20%.
[0054] Pure Mg is preheated at 300–400 °C for 30–90 min, then heated to 680–695 °C to completely melt it, yielding molten magnesium. Pure Zn, Mg-Sm master alloy, Mg-Mn master alloy, Mg-Y master alloy, and Mg-Ca master alloy are preheated at 100–200 °C for 30–100 min, and then added in batches to the molten magnesium according to the alloy composition ratio. After the addition is complete, the alloy melt is heated to 700–720 °C and held for 5–10 min, followed by refining with argon gas. After refining, slag is removed and the mixture is allowed to stand. The alloy melt is then poured into a mold preheated to 220–240 °C, and after cooling, a magnesium alloy ingot is obtained.
[0055] S2: Homogenization treatment: The magnesium alloy ingot obtained in step S1 is heated to 500 ℃ and held for 8 h, and then water-quenched to room temperature to obtain a homogenized magnesium alloy ingot.
[0056] S3: Rolling and Annealing: The homogenized magnesium alloy ingot obtained in step S2 is processed into a slab with an initial thickness of 5 mm, and then rolled to the target thickness of 1.5 mm using a unidirectional rolling process. Before each rolling pass, the slab is held at 320 ℃ for 10 min; except for the last pass, the reduction rate per pass is approximately 15%, and the reduction rate of the last pass is adjusted according to the target thickness.
[0057] After rolling, the plate is heated to 420 ℃ and held for 30 min, then water-cooled to room temperature to obtain annealed Mg-1.5Zn-1Sm-0.2Mn-0.1Ca alloy plate.
[0058] To evaluate the high-temperature microstructure and performance stability of the alloy sheet, the annealed alloy sheet obtained in step S3 was subjected to a heat exposure treatment at 200 ℃ for 1000 h. After the heat exposure, the sample was air-cooled to room temperature and tensile property tests were performed. The test results showed that after heat exposure at 200 ℃ for 1000 h, the room temperature yield strength of the alloy sheet increased to 220 MPa without a decrease in plasticity, exhibiting good high-temperature microstructure and mechanical property stability.
[0059] Figure 1 The room temperature engineering stress-strain curve and cupping diagram of the alloy sheet of Example 1 are shown. The annealed Mg-1.5Zn-1Sm-0.2Mn-0.4Y-0.1Ca alloy sheet prepared in this example has a yield strength of 180 MPa, an elongation of 18%, and an Eriksen cupping value of 7.6 mm.
[0060] Figure 2 The average corrosion rate of the alloy sheet from Example 2 after immersion in a 3.5% (w / w) NaCl aqueous solution for 7 days is shown, measured using both the hydrogen evolution method and the weight loss method. Wherein, P... H P represents the average corrosion rate calculated using the hydrogen evolution method. W The average corrosion rate is calculated using the weight loss method, and the unit is mm / year.
[0061] Depend on Figure 2 It can be seen that the average corrosion rate measured by the hydrogen evolution method is 1.16 mm / year, while the average corrosion rate measured by the weight loss method is slightly higher than that measured by the hydrogen evolution method. The corrosion rates obtained by the two methods are at similar levels, indicating that the test results have good consistency. The above results show that the alloy of Example 2 has good corrosion resistance in a 3.5% NaCl aqueous solution.
[0062] Figure 3 The room temperature engineering stress-strain curves of the alloy sheet from Example 3 after heat exposure at 200 °C for 1000 h are shown. Figure 3 It can be seen that after long-term heat exposure, the room temperature yield strength of the alloy sheet in Example 3 increased to 220 MPa and the plasticity did not decrease. No mechanical property deterioration occurred, indicating that the alloy has good high-temperature microstructure and mechanical property stability.
[0063] Comparative Example 1:
[0064] CN105349861B discloses a method for preparing a high-ductility magnesium alloy sheet. The Mg-Zn-Er magnesium alloy used in this method comprises 0.5% Zn and 0.5% Er by mass percentage, with the balance being Mg and unavoidable impurities.
[0065] This method employs a two-stage variable-temperature rolling process, consisting of high-temperature rough rolling, low-temperature finish rolling, and post-rolling annealing. In its optimal embodiment, the homogenized slab is first subjected to multi-pass rough rolling at 400 °C, with a single-pass reduction of 10%–15% and a total reduction of approximately 50%. Subsequently, the temperature is lowered to 300 °C for multi-pass finish rolling, achieving a cumulative total reduction of over 80%. Finally, the slab undergoes annealing at 300 °C for 30 minutes. After this variable-temperature rolling and annealing process, the highest Eriksen cupping value of the sheet metal is 5.67 mm.
[0066] Compared with the above methods, this invention employs a multi-element microalloying composition design, combined with homogenization treatment, 320 ℃ constant temperature multi-pass unidirectional rolling, and post-rolling annealing. This eliminates the need for staged variable-temperature rolling by switching rolling temperatures, resulting in fewer process steps, more stable parameter control, and better suitability for continuous industrial production. The Eriksen cupping value of the magnesium alloy sheet obtained in Example 1 reached 7.6 mm, higher than the 5.67 mm disclosed in the optimal embodiment of CN105349861B. This indicates that the synergistic regulation of the composition and processing technology described in this invention can more significantly weaken the rolling surface texture and obtain superior room temperature stamping performance.
[0067] Comparative Example 2:
[0068] CN109182859A discloses a method for preparing high-formability magnesium alloy sheets by composite deformation. The AZ31 magnesium alloy sheet used in this method comprises, by mass percentage, 3% Al, 1% Zn, and 0.3% Mn, with the balance being Mg.
[0069] The method sequentially includes pre-heat treatment, first transverse rolling, intermediate heat treatment, transverse compression, post-heat treatment, and second transverse rolling. In Example 1, the plate is first held at 300 ℃ for 3 h and then water-cooled, followed by transverse rolling deformation of 3%; then held at 300 ℃ for 1 h and water-cooled, followed by transverse compression deformation of 3%; then held at 300 ℃ for 1 h again and water-cooled, and finally transverse rolling deformation of 1%. After the above composite deformation treatment, the Eriksen cupping value of the plate increases from 2.8 mm to 5.3 mm.
[0070] Compared with the above methods, the present invention employs a process combining homogenization treatment, multi-pass unidirectional rolling, and post-rolling annealing, eliminating the need for multiple water-cooling heat treatments and transverse compression deformation between different deformation stages, thus reducing the number of process steps. The Eriksen cupping value of the magnesium alloy sheet obtained in Example 2 reached 7.6 mm, higher than the 5.3 mm disclosed in Example 1 of CN109182859A, indicating that the composition and processing technology described in this invention can achieve good room temperature stamping performance.
[0071] Comparative Example 3:
[0072] CN108300918B discloses a calcium-rare-earth magnesium alloy sheet with high room temperature forming performance and its preparation method. The magnesium alloy used in Example 9 of this patent includes Al 3%, Zn 1%, Ca 0.4%, Gd 0.4% and Mn 0.2% by mass percentage, with the balance being Mg, and the total mass fraction of alloying elements is 5.0%.
[0073] In this embodiment, a magnesium alloy ingot was held at 450 °C for 12 h, and then a 10 mm thick slab was hot-rolled at 400 °C in multiple passes to a thickness of 1 mm, with a total reduction of 90%. After each rolling pass, the slab was held at 400 °C, and then annealed at 350 °C for 60 min. The final magnesium alloy sheet had an Eriksen cupping value of 5.0 mm.
[0074] Compared with the above methods, the present invention uses a lower amount of alloying elements and prepares magnesium alloy sheets through homogenization treatment, multi-pass unidirectional rolling at 320°C, and short-time annealing at 420°C. The Eriksen cupping value of the magnesium alloy sheet obtained in Example 2 reaches 7.6 mm, which is higher than the 5.0 mm disclosed in Example 9 of CN108300918B, indicating that the composition and processing technology described in the present invention are beneficial to improving the room temperature stamping performance of magnesium alloy sheets.
[0075] General Explanation:
[0076] In summary, this invention utilizes the synergistic microalloying design of elements such as Zn, Sm, Mn, Y, and Ca, combined with homogenization treatment, unidirectional rolling, and post-rolling annealing processes, to regulate the grain structure, texture, and second-phase distribution of the alloy.
[0077] In one specific embodiment, a magnesium alloy ingot is homogenized at 500 °C for 8 h, then water-quenched and processed into a slab with an initial thickness of 5 mm. Subsequently, the slab is rolled to 1.5 mm using a multi-pass unidirectional rolling process at 320 °C, with a holding time of 10 min before each rolling pass. After rolling, it is annealed at 420 °C for 30 min and then water-cooled. This process mainly uses conventional melting and casting, heat treatment, and unidirectional rolling equipment, and the process route is relatively simple, showing potential for application in existing magnesium alloy sheet production lines.
[0078] The magnesium alloy sheet prepared in Example 2 achieved an Eriksen cupping value of 7.6 mm. After immersion in a 3.5% NaCl aqueous solution for 7 days, the average corrosion rate measured by the hydrogen evolution method was approximately 1.16 mm / year, demonstrating good room temperature stamping performance and corrosion resistance. Related heat exposure tests showed that after heat exposure at 200 °C for 1000 h, the room temperature yield strength of the magnesium alloy sheet increased to 220 MPa without a decrease in plasticity, exhibiting good high-temperature microstructure and mechanical property stability.
[0079] The magnesium alloy and its preparation method described in this invention can be used to prepare structural components for new energy vehicles, housings for electronic products, electronic heat dissipation components, and other lightweight thin-plate components, providing a technical solution for the development and application of low-alloy, high-formability, corrosion-resistant, and heat-resistant magnesium alloy sheets.
[0080] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Those skilled in the art can make equivalent substitutions, simple changes or improvements to the alloy composition, process steps and process parameters without departing from the concept of the present invention.
[0081] Where there is no technical conflict, the technical features in the above embodiments and preferred embodiments can be combined with each other. All modifications, equivalent substitutions, and improvements made within the spirit and principles of this invention should be included within the scope of protection defined by the claims of this invention.
Claims
1. A multi-element microalloyed high-formability, corrosion-resistant, and heat-resistant magnesium alloy, characterized in that, The magnesium alloy is composed of the following components by mass percentage: Zn 1.5%, Sm 1.0%, Mn 0.2%, Y 0.4%, Ca 0.1%, with unavoidable impurities totaling no more than 0.05%, and the balance being Mg; the total mass fraction of alloying elements in the magnesium alloy is 3.2%.
2. A method for preparing a multi-element microalloyed high-formability, corrosion-resistant, and heat-resistant magnesium alloy, applied to the multi-element microalloyed high-formability, corrosion-resistant, and heat-resistant magnesium alloy as described in claim 1, characterized in that, Includes the following steps: S1, Casting: Prepare pure Mg, pure Zn, Mg-Sm master alloy, Mg-Mn master alloy, Mg-Y master alloy, and Mg-Ca master alloy according to the composition ratio of the magnesium alloy; melt pure Mg under a mixed protective atmosphere composed of CO2 and SF6 to obtain magnesium liquid; add the remaining raw materials except pure Mg to the magnesium liquid in batches after preheating at 100-200 °C for 30-100 min; after the addition is completed, heat the magnesium liquid to 700-720 °C and hold for 5-10 min, then purge with argon gas for refining, remove slag and let stand, then pour the magnesium liquid into a mold preheated to 220-240 °C, and obtain magnesium alloy ingots after cooling; wherein, the volume fraction of CO2 in the mixed protective atmosphere is 80%-90% and the volume fraction of SF6 is 10%-20%; S2, Homogenization treatment: The magnesium alloy ingot obtained in S1 is subjected to homogenization treatment, and then water quenched to room temperature to obtain a homogenized magnesium alloy ingot. S3, Rolling and Annealing: The homogenized magnesium alloy ingot obtained in S2 is rolled and then annealed to obtain the multi-element micro-alloyed high formability, corrosion resistance and heat resistance magnesium alloy sheet.
3. The method for preparing a multi-element microalloyed high-formability, corrosion-resistant, and heat-resistant magnesium alloy according to claim 2, characterized in that, In step S1, the added Mn element combines with iron impurities in the melt to form high-melting-point intermetallic compounds that settle and separate. The Y element reacts with oxygen and iron impurities in the melt to generate high-melting-point rare earth oxides and rare earth-iron intermetallic compounds, some of which float to the surface as slag or settle, thus achieving the purification of impurities in the melt.
4. The method for preparing a multi-element microalloyed high-formability, corrosion-resistant, and heat-resistant magnesium alloy according to claim 2, characterized in that, In step S2, the homogenization treatment temperature is 500 ℃, the holding time is 8 h, and after the homogenization treatment is completed, the water is quenched to room temperature.
5. The method for preparing a multi-element microalloyed high-formability, corrosion-resistant, and heat-resistant magnesium alloy according to claim 2, characterized in that, In S3, the rolling process adopts a unidirectional rolling process. The initial thickness of the plate before rolling is 5 mm, and the target thickness of the plate after rolling is 1.5 mm. Before each rolling pass, the plate is kept at 320 ℃ for 10 min. Except for the last pass, the single-pass reduction rate is 15%, and the reduction rate of the last pass is adjusted according to the target thickness.
6. The method for preparing a multi-element microalloyed high-formability, corrosion-resistant, and heat-resistant magnesium alloy according to claim 2, characterized in that, In step S3, the annealing temperature is 420 ℃, the holding time is 30 min, and water cooling is performed after the annealing process.
7. The method for preparing a multi-element microalloyed high-formability, corrosion-resistant, and heat-resistant magnesium alloy according to claim 2, characterized in that, The obtained magnesium alloy sheet has an Eriksen cup convexity of 7.6 mm; after being immersed in a 3.5% NaCl aqueous solution for 7 days, the average corrosion rate of the magnesium alloy sheet, measured by the hydrogen evolution method, is 1.16 mm / year; after being exposed at 200℃ for 1000 hours, neither the strength nor the plasticity showed a significant decrease.
Citation Information
Patent Citations
A kind of rapid rolling formable magnesium metal plate and its rolling method
CN105349861B
A calcium-rare-earth magnesium alloy sheet with high room temperature forming performance and its preparation method
CN108300918B
Method for preparing high-formation-property magnesium alloy panel by composite deformation
CN109182859A